KEMAMPUAN KEMAMPUAN MEMBUAT RINGKASAN TEKS BACAAN PADA SISWA KELAS V SEMESTER GENAP SD NEGERI 1 GULAK GALIK TELUK BETUNG UTARA BANDAR LAMPUNG TAHUN PELAJARAN 2018/2019 - Parnandes, Pastry Nelly (Pedagogia: Jurnal Ilmiah Pendidikan Dasar Indonesia, 2020)
The purpose of this study was to find out and describe how the level of students' ability to make a reading text summary in fifth grade students of SD Negeri 1 Teluk Betung Galik North Bandar Lampung 2018/2019 academic year. This study uses descriptive quantitative method, while the technique of collecting data with test techniques. The population of this study amounted to 29 students and the number of samples was determined by the entire population, namely 25 people. Analyze data using percentages. The results showed that the ability to compile a reading text summary for odd grade V students of SD Negeri 1 Teluk Betung Galik North Bandar Lampung 2018/2019 academic year was included in the Enough category. This is known from the average value obtained by students which is 72.4. The average value obtained by students based on aspects of the assessment is as follows: (1) the summary aspect contains the main thoughts of each paragraph is 74 these values ​​include the level of ability Enough; (2) sentence wrangling is 70 of these values ​​including sufficient level of ability, (3) easy-to-understand language obtains 85 values ​​including excellent ability level, (4) summary contents using summary author's own language scores 68 of these values ​​including ability level Enough, (5) word choice (diction) obtains 66 values ​​of this value including sufficient level of ability, and (6) the use of punctuation / punctuation scores of 71 this value includes sufficient level of ability.